Long-term Fate of Denervated Skeletal Muscle After Microvascular Flap Transfer. Issue 6 (June 2018) - Chang, Hak; Hwang, SeungHwan; Lim, SooA; Eo, SuRak; Minn, Kyung Won; Hong, Ki Yong
Abstract : Background: Muscle flap is a valuable option in soft tissue reconstruction. Denervated skeletal muscle is known to undergo degeneration. However, information regarding histological and genetic changes in muscle free flap without reinnervation over long-term follow-up remains unclear. Methods: We collected flap muscles obtained during secondary exploration surgery after more than 15 years of previous muscle free flap without reinnervation. Compared with normal muscle and fat, histomorphometric and gene expression analysis of flap muscle were performed. Results: During the study period, we collected 5 samples of previous muscle free flap. The mean ± SD postoperative duration after free flap was 18.6 ± 4.0 years. All flap muscles were replaced with adipose tissue based on gross and histological findings. In flap muscle, the expression of gene related to muscle-specific MYH2 gene was downregulated, whereas the expression of genes related to adipose, fibroadipogenic progenitor, and blood vessel was upregulated compared with that of normal muscle. Vascular density and pattern were also similar to those in normal fat. Conclusions: We demonstrated that muscle free flap without reinnervation eventually converts into adipose tissue regardless of spontaneous reinnervation during muscle regeneration. The long-term findings of the present study will be valuable for muscle flap selection and prognosis.